O impacto das tecnologias de comunicação e a criação de uma narrativa diferenciada nos roteiros de radiojornais - Bufarah Junior, Alvaro (2019)
The new communication technologies have irreversibly impacted the production processes and the consumption of news. Among the means of communication, the radio is the one that has been adapting over the course of its history to the various moments of technological breakdown through which it has passed. These new changes in structure, diffusion, production, professional profile, among others, led to substantial changes in the profiles of the journalistic narratives of various radio programs. We can evaluate this process by comparing and analyzing radiojournalistic scripts before and after the impact of the new technologies in the 1990s. We can note that we have had a change in the language of these programs with the reduction of the number of texts produced, to the publication of texts presented in sites, social networks, and mobile apps. This work seeks to analyze the processes and their consequences for the structuring of radio journalistic programs post-communication technologies, indicating the changes of languages and how the narratives are structured in this new context